2013
DOI: 10.11111/jkana.2013.19.5.658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decision Making Competency, Nursing Professionalism, and Job Satisfaction on Turnover Impulse among Nurses

Abstract: Purpose:The study was undertaken to investigate effects of decision making competency, nursing professionalism and job satisfaction on turnover impulse, and identify factors contributing to turnover impulse among nurses. Methods: The study was a descriptive study with 231 nurses from 4 general tertiary hospitals participating. Data were collected during March, 2013 using a structured self-report questionnaire. Decision making competency, nursing professionalism, and job satisfaction were measured with validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 16 publications
(8 reference statements)
0
3
1
Order By: Relevance
“…The average score for nursing professionalism was 3.25 out of 5, lower than that of tertiary hospital nurses (3.4) reported by Yoon et al [31]. In this study, social recognition scored the lowest among the sub-factors (2.79 out of 5), whereas Yoon et al [31] reported lower scores for selfconcept of the profession (2.58) and the role of nursing (2.63). This contradiction can be explained by the fact that most participants (95.2%)…”
Section: Discussioncontrasting
confidence: 69%
“…The average score for nursing professionalism was 3.25 out of 5, lower than that of tertiary hospital nurses (3.4) reported by Yoon et al [31]. In this study, social recognition scored the lowest among the sub-factors (2.79 out of 5), whereas Yoon et al [31] reported lower scores for selfconcept of the profession (2.58) and the role of nursing (2.63). This contradiction can be explained by the fact that most participants (95.2%)…”
Section: Discussioncontrasting
confidence: 69%
“…In terms of marital status, single (unmarried) men are more vulnerable to switchovers than married ones. 13 In general, research demonstrates that female staff, married ones, those with higher education and permanent professions, and those with advanced increments and high salaries are eventually more likely to stay in the clinic. 23,24 The findings of this study also revealed that medical staff felt a greater imbalance in ERI but they did not want to leave their profession because they had gone through the critical condition; moreover, the unofficial staff was more likely to intend to leave their profession.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…organization is happy and satisfied with their profession, they are loyal to their organization and rarely leave their profession. 13 Furthermore, effort and reward equity at work affect staff's work-related attitudes, especially job satisfaction and the intention to leave an organization. 14 The intention of the staff to leave their professions can be explained as rational choices taken at a cognitive end regarding the present profession or organizations or both.…”
mentioning
confidence: 99%
“…This increase in the number of male nurses could be attributed to changing social norms that led to gender stereotypes being less pervasive and allowed individuals to select jobs that best suit their aptitude, and to the increased flexibility of members of the younger generation in terms of their job perceptions [4]. In addition, important factors that influence men's decision to enter nursing include the ease of obtaining a nursing job [5], the relatively high salary drawn as a new employee [6], and the anticipation of faster achievement in a field in which men are a minority [7,8].…”
Section: Introductionmentioning
confidence: 99%